THE ROLE OF THE UNITED NATIONS CHILDREN'S FUNDS (UNICEF) IN HANDLING ROHINGYA CHILDREN REFUGEES IN BANGLADESH 2016-2018 - Anne F. Damanik (PT. Radja Intercontinental Publishing, 2024)
Currently, there are still many countries that are still living closely together with conflicts that have not been resolved day by day. The world is still mourning the many conflicts that occur due to political, economic, socio-cultural problems and ethnic, religious and racial differences.The United Nations Children's Fund (UNICEF) is an organization formed by the United Nations (UN) under the UN General Assembly. The UN has a system known as